Compliance Determinants of Mothers in Full Child Immunisation in Bangkalan District - Chalidyanto, Djazuly (2017)
Child immunisation is one of the cost-effective interventions in response to health problems and it provides protection against a variety of health problems for children. Universal Child Immunisation (UCI)’s achievement is a projection of the coverage of complete child immunisation. Child immunisation coverage in Bangkalan in 2011 had a gap compared to the target. The study aims to analyse the factors that influence mothers’ compliance with child immunisation based on maternal characteristics, community support, and health workers in Bangkalan district. This research used a cross-sectional design and the populations were all mothers of children aged 12-24 months. The analysis was then continued using Path Analysis. The data was collected using a multi-stage sampling method. The samples included 360 respondents selected by the snowball technique. The results reveal that 37.3% of infants had been fully immunised on schedule and this indicates the mothers’ compliance with child immunisation. The Path Analysis Model is able to predict immunisation compliance. The predictive factors are Community Support, Mother’s Characteristics, Health worker, Service, and the Mother’s Factors. Result showed that mother’s characteristics and the health service directly affected the mother’s compliance of child immunisation. Community support, health manpower and the mother’s factors only have indirect effects.